2020
DOI: 10.1101/2020.09.21.307223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheClostridioides difficilespecies problem: global phylogenomic analysis uncovers three ancient, toxigenic, genomospecies

Abstract: Clostridioides difficile infection (CDI) remains an urgent global One Health threat. The genetic heterogeneity seen across C. difficile underscores its wide ecological versatility and has driven the significant changes in CDI epidemiology seen in the last 20 years. We analysed an international collection of over 12,000 C. difficile genomes spanning the eight currently defined phylogenetic clades. Through whole-genome average nucleotide identity, pangenomic and Bayesian analyses, we identified major taxonomic i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The MLST for this strain was unusual, as it was classified into clade 1 despite containing binary toxin genes in a complete CDT locus. The presence of binary toxin genes is a feature common in C. difficile clades 2 and 5, but rare in clade 1 (42). Thus, an ANI analysis was performed, which indicated that this newly characterised strain was more related to clade 2 than clade 1 C. difficile, as expected from the toxin gene profile.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The MLST for this strain was unusual, as it was classified into clade 1 despite containing binary toxin genes in a complete CDT locus. The presence of binary toxin genes is a feature common in C. difficile clades 2 and 5, but rare in clade 1 (42). Thus, an ANI analysis was performed, which indicated that this newly characterised strain was more related to clade 2 than clade 1 C. difficile, as expected from the toxin gene profile.…”
Section: Discussionmentioning
confidence: 85%
“…A summary of MIC values and genotypic resistance determinants of 37 sequenced C. difficile strains is available in Supplementary Table S2. Of these strains, 31 had high-level resistance to clindamycin: 23 strains carried an erm(B) gene, five carried an erm(G) gene and three carried a gene encoding an rRNA adenine N(6)-methyltransferase family protein, the closest match to which in the CARD database was the Erm (42) protein [39% identity, E-value = 1.19E-53] (38). This newly characterised gene was given the name erm(52).…”
Section: Genotypic Resistance Determinants In Thai C Difficilementioning
confidence: 99%
“…As a result, it may be difficult to properly discriminate these two clades by this method. The use of ANI analysis, which involves the whole genome rather than a specific set of housekeeping genes, can help in the correct classification of some borderline strains as shown in a previous study (40). According to the ANI analysis, it is likely that this newly described C. difficile ST 692 belongs to clade 2 and is related to C. difficile RT 027.…”
Section: Discussionmentioning
confidence: 92%
“…The MLST result for this strain was unusual, as it was classified into clade 1 despite containing binary toxin genes in a complete CDT locus. The presence of binary toxin genes is a feature common in C. difficile clades 2 and 5 but rare in clade 1 (40). Thus, an ANI analysis was performed, which indicated that this newly characterised strain was more related to clade 2 than clade 1 C. difficile , as expected from the toxin gene profile.…”
Section: Discussionmentioning
confidence: 99%
“…Using WGS, the presence of divergent toxin genes can be confirmed. Although ultimately, these divergent strains of C. difficile may be reclassified at either the species or genus level, currently they still need to be considered in any diagnostic algorithm [18]. Thus, sequencing can help distinguish mild CDI from colonization, as well as detect cases that may be otherwise missed by current diagnostic approaches, for example, in cases where the fecal toxin/toxin gene detection results do not correlate with the clinical data and thus require C. difficile culture as a confirmation test.…”
Section: Can Sequencing Improve the Diagnosis And Management Of Clostridioides Difficile Infection?mentioning
confidence: 99%